Perioperative Optimization of Patients Undergoing Bariatric Surgery - C. E. Owers; Y. Abbas; R. Ackroyd; N. Barron; M. Khan (Journal of Obesity)
Bariatric surgery is fast becoming an efficient and safe method of weight reduction, especially for patients in whom conservative measures have failed. As the obese population of the world increases, so will the number of patients requesting or requiring surgical weight loss methods. Bariatric patients however have numerous co-morbidities that make their operative course more difficult, and therefore is important to have a good understanding of the important issues surrounding their pre, peri and post operative management. This article aims to educate the reader about optimal management of the bariatric surgical patient.